Disusing the mobility aids devices in the elderlies: how much and why? - Zohre Rahaei; maryam tavakoli; Alireza Beigomi; Sara Jambarsang (Shahid Beheshti University of Medical Sciences, 2022)
Background: Given that society is rapidly aging, identifying the problems of the elderly can help society and individuals, so in this study investigates the abundance of elderlies in need of mobility aids devices and the factors related to their disuse. Methods: This cross-sectional study was performed on 209 elderlies who selected by random sampling in Taft city. Data gathering tools were MMSE and TUG tests, and a researcher-made questionnaire. The data were analysed Mann-whitney & chi-square test. Result: Among the elderlies, 75.12% of them required to use mobility aids devices that 49% of these people did not use these devices due to the feeling of shyness, needless, ignorance of the device's necessity, and negative attitude of other people. Conclusion: Despite the need of most elderly for motor assisted devices, almost half of them do not use these devices because of educational and attitudinal reasons.